2014
DOI: 10.1186/bf03351712
|View full text |Cite
|
Sign up to set email alerts
|

Local time features of geomagnetic jerks

Abstract: The geomagnetic jerk amplitudes, which are defined as abruptness of changes in the trends of geomagnetic time series, are investigated with geomagnetic monthly means computed from hourly mean values at each local time.A statistical time series model in which the trend component is expressed by a second order spline function with variable knots is constructed for each time series. The optimum parameter values of the model including positions of knots are estimated by the maximum likelihood method, and the optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Other recent works have confirmed the internal origin of jerks, for example, Le Huy et al (1998) who performed spherical harmonic models of the 1969, 1978 and 1991 events ( X , Y and Z components). In addition, Nagao et al (2002) investigated geomagnetic monthly means, obtained from hourly mean values at each local time, of the three magnetic components of the same jerk. They concluded that the distribution of the jerk is independent of local time and that it cannot be explained by external currents.…”
Section: Introductionmentioning
confidence: 99%
“…Other recent works have confirmed the internal origin of jerks, for example, Le Huy et al (1998) who performed spherical harmonic models of the 1969, 1978 and 1991 events ( X , Y and Z components). In addition, Nagao et al (2002) investigated geomagnetic monthly means, obtained from hourly mean values at each local time, of the three magnetic components of the same jerk. They concluded that the distribution of the jerk is independent of local time and that it cannot be explained by external currents.…”
Section: Introductionmentioning
confidence: 99%
“…With observatory data, jerk occurrence times for all sv components at the Earth's surface have already been detected, for example, by De Michelis et al (2000), Nagao et al (2002) and Nagao et al (2003). Concerning the CMB region, an investigation by Dormy & Mandea (2005) for a non‐conducting mantle showed that it was not possible to find a sharp jerk signal in the component at the CMB.…”
Section: Resultsmentioning
confidence: 99%
“…It can also be equivalently described as a jump in the time derivative of the geomagnetic sv, that is, in the geomagnetic secular acceleration. In former studies, the surface distribution of these jumps was addressed by the term ‘jerk morphology’ (De Michelis et al 1998; 2000; Le Huy et al 2000; Nagao et al 2002; Pinheiro & Jackson 2008). While this distribution was referred to a fixed mean jerk occurrence time, we can extend this concept to a ‘dynamical jerk morphology’, which is composed of jumps moving at the Earth's surface and at the CMB: Related to each secular acceleration component, a temporally variable surface function can be defined.…”
Section: Geomagnetic Jerksmentioning
confidence: 99%
See 2 more Smart Citations